A humán erőforrás menedzsment funkciók fejlődése 2. rész: A "bürokrata” szakasz jellemzői = Development of function of human resource management part II. - Gulyás, László; Turcsányi, Enikő (Közép-Európai Közlemények, 2018)
According to Torrington-Hall, the HR-functions developed six phases, from the industrial revolution to present day. In our paper we analyze the development of functions of human resource management. Our essay consists of two parts. In the first part of this essay we survey the features of third phase – this is called bureaucrat – in England. In the second part of this essay we survey the features of third phase in Hungary at between the First World War and Second World War.